2014
DOI: 10.1016/j.jand.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Financial Incentives for Dietary Behavior Change

Abstract: In light of the obesity epidemic, there is growing interest in the use of financial incentives for dietary behavior change. Previous reviews of the literature have focused on randomized, controlled trials and found mixed results. The purpose of this systematic review is to update and expand upon previous reviews by considering a broader range of study designs, including RCTs, quasi-experimental, observational, and simulation studies testing the use of financial incentives to change dietary behavior and to info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 31 publications
1
53
0
Order By: Relevance
“…However, on the basis of Skinner's behaviorism, money can be used as a form of inducement or motivation in order to elicit positive responses in a person-for example exercising at a gym to get reward points. These points have monetary value and may then be used for the purchase of various goods and services [4]. The argument here is that the idea of money as health is not without limitations or exclusions.…”
Section: Discussionmentioning
confidence: 99%
“…However, on the basis of Skinner's behaviorism, money can be used as a form of inducement or motivation in order to elicit positive responses in a person-for example exercising at a gym to get reward points. These points have monetary value and may then be used for the purchase of various goods and services [4]. The argument here is that the idea of money as health is not without limitations or exclusions.…”
Section: Discussionmentioning
confidence: 99%
“…19 Despite widespread implementation of FI-based workplace wellness policies, the effects of FI on exercise or healthy diet initiation and maintenance and behavior change in adults remain unclear due to mixed findings. While most report FI to be effective, these results tend to be short lived, 18, 22 and there is little evidence indicating FI lead to sustained weight loss maintenance. 20 FI remain to be a potentially useful tool in aiding behavior modification, but further investigation is warranted.…”
Section: Introductionmentioning
confidence: 96%
“…3 FI has also been linked to positive effects on healthy food purchases, consumption, and dietary behavior modification in short-term interventions. 19, 22 Modest FI in workplace weight loss interventions have been shown to motivate overweight employees to lose weight 23 , improve health outcomes (weight loss) in the short-term, and incite some lifestyle and behavior modification. 18 Additionally, FI have been linked to increased engagement and adherence to healthful behavioral change, perhaps even after the incentive is withdrawn, 3,21 which may further lead to improved SE.…”
Section: Introductionmentioning
confidence: 99%
“…As such, promising research in adults has found that incentives can positively influence health-related behaviour change in the short term 16–18. For example, several systematic reviews have demonstrated positive outcomes as a result of financial incentives in terms of healthy eating19–21 and positive effects on exercise behaviour 2223 Many of the studies included in the reviews have acknowledged the need for more research to determine specific information on the type, timing and magnitude of incentives needed to motivate individuals to change their behaviour, as well as disincentives 19.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several systematic reviews have demonstrated positive outcomes as a result of financial incentives in terms of healthy eating19–21 and positive effects on exercise behaviour 2223 Many of the studies included in the reviews have acknowledged the need for more research to determine specific information on the type, timing and magnitude of incentives needed to motivate individuals to change their behaviour, as well as disincentives 19. There are also mixed findings on whether incentives are more useful for simple one-off behaviours (eg, attendance at a vaccination) rather than complex health behaviours such as dietary behaviour change, and if specific groups may benefit more from incentive schemes 17.…”
Section: Introductionmentioning
confidence: 99%